Climate Change Impacts on the Indus River Basin: Hydrology, Water Quality, and Treaty Implications - Muhammad Khizar; Shah Nawaz; Hassan Bashir; Muhammad Aqeel (iRASD Journal of Energy & Environment)
The Indus River is highly sensitive to climate variability because most of its flow depends on Himalayan snow and glacier melt as well as monsoon rains. Climate change induces shifts in precipitation patterns, accelerating glacier retreat, and increasing the frequency of floods and droughts in the basin. The objective of this study was to analyze the quality of the Indus water and to assess the effects of climate on it, i.e. how changes in climate affect the hydrological cycle, glacier dynamics and water quality in the Indus basin.  Using field data from the Kunar and Kabul rivers (tributaries of the Indus) and a review of climate impacts, significant regional differences in water quality parameters were noted and climate-induced hazards (e.g. floods, droughts, salinity intrusion, ecosystem stress) outlined. The implications of these changes for water security, agriculture and Indo-Pak water governance were studied. It was noted that the Indus Waters Treaty currently lacks provisions for climate-induced variability. Climate change is altering the Indus hydrological regime and water quality, posing challenges to sustainable water management and regional stability.